IMPLEMENTASI PEMBELAJARAN QUR-ANY 2 DALAM PENINGKATAN PEMAHAMAN TERJEMAH AL-QUR’AN PERKATA DI MTS AL-URWATUL WUTSQO BULUREJO DIWEK JOMBANG - Moch. Sya’roni Hasan; Mar’atul Azizah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2021)
Abstract: This study seeks to discuss the implementation of Qur-any 2 learning inimproving students' understanding of the word translation of the Qur'an at MTs alUrwatul Wutsqo Jombang. Field research (field research). This study uses adescriptive qualitative approach. Data collection techniques through interviews,observation, and documentation. Furthermore, data analysis was carried out usingdescriptive qualitative analysis methods. From the results of the study of Qur-any 2research, it was found that there were 1. educators must attend training and coachingfor Qur-any educators first. 2. The implementation process applies the principle of2x3 learning, namely imitating and repeating in terms of sound, reading and writing.3. Evaluation is done by the educator giving verses of the Qur'an and then studentsare assigned to memorize it then translate the pieces which are then interpreted andgive examples of how to practice the verse in life. Increasing students' understanding,namely: 1. Applying or translating the verses of the Qur'an, 2. Knowing how topractice the verses of the Qur'an. supporting and inhibiting factors of learninginclude: teachers, media, infrastructure, environment. Based on the analysis of thedata sources obtained, it can be concluded that learning Qur-any 2 includes planning,implementation, and evaluation. Increasing students' understanding, namely: beingable to translate, interpret, and know how to practice it. And supporting and inhibitingfactors include, teachers, goals, methods, media, environment. It is important foreducators to continue to motivate students to become human beings who understandthe Qur'an and are able to practice it in life.Keywords: Learning Qur-any 2, Increasing Understanding.